2018
DOI: 10.2147/ppa.s154181
|View full text |Cite
|
Sign up to set email alerts
|

Preference for a prefilled syringe or an auto-injection device for delivering golimumab in patients with moderate-to-severe ulcerative colitis: a randomized crossover study

Abstract: PurposeSimponi® (golimumab, MSD) is a fully human monoclonal antibody against tumor necrosis factor alpha administered subcutaneously using an autoinjector or a prefilled syringe. This study examined preference for administration of golimumab by autoinjector or prefilled syringe in patients with moderate-to-severe ulcerative colitis (UC).Patients and methodsThis was a multicenter, open-label, randomized crossover trial (EudraCT no 2014-000656-29). Patients with moderate-to-severe UC were randomized 1:1 to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…As this study was performed for healthy volunteers, and each volunteer received a single injection with only one device, one limitation was that patient preference for the AI or APFS device was not explored. Patient preference for AI over APFS has been reported for selfadministration of arthritis medication, while no device preference was described in a migraine study (8)(9)(10). Future studies should be performed to determine device preference for patients receiving benralizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this study was performed for healthy volunteers, and each volunteer received a single injection with only one device, one limitation was that patient preference for the AI or APFS device was not explored. Patient preference for AI over APFS has been reported for selfadministration of arthritis medication, while no device preference was described in a migraine study (8)(9)(10). Future studies should be performed to determine device preference for patients receiving benralizumab.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to provide patients device options to support their satisfaction and adherence. Several studies for patients with arthritis and ulcerative colitis have indicated that patients prefer AI over APFS for selfadministration of their medications, with reasons including ease of use, satisfaction, and acceptability (8,9). In a report on self-administration of migraine medication, patients found both devices equally easy to use and were comfortable using either (10).…”
Section: Introductionmentioning
confidence: 99%
“…Ease of training and total training time variables varied significantly (p = 0.01 and p = < 0.001, respectively) between the four training locations (home, hospital, doctor's office, or other) ( Table 7). Overall, the median rating (interquartile range [IQR]) for ease of training was higher for respondents trained in hospital or a doctor's office (7 [6,7] for both locations), compared with respondents trained at home (6 [5,7]) or in other locations (6 [4,7]). The total training time was lowest in those trained in hospital, with a median time of 1 h, whereas in all other locations (home, doctor's office, and other), the median time was 4 h. No significant difference was found between the knowledge of trainer and the different training locations (p = 0.21).…”
Section: Associations Between Training Variablesmentioning
confidence: 99%
“…Favorable infusion and training characteristics were defined as follows: a) Favorable training: (i) efficiency of training, (ii) the respondent's self-perception of their trainer (high [6,7] scores for competence and knowledge of trainer, and satisfaction with quality of training), and (iii) absence of training barriers. Efficient training characteristics included: requiring ≤3 training sessions; a total SCIG training time ≤4 h; individual training sessions ≤2 h; ease of training rated 6-7; and confidence after training rated 6-7. b) Efficient infusions: defined as reported actual infusion time of ≤2 h; infusion preparation duration of ≤20 min; and total infusion duration (including preparation and clean-up) of ≤3 h, or lower frequency of infusions.…”
Section: Training and Infusion Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation